2004
DOI: 10.1002/pssc.200304879
|View full text |Cite
|
Sign up to set email alerts
|

Spherical quantum dot under an electric field

Abstract: PACS 73.21.LaWe investigate the effect of an electric field applied to a spherical quantum dot on the energy groundstate of carriers in the quantum dot using an infinite confining potential well model. We perform a simple variational calculation for low electric fields and we find a quadratic shift of the energy levels with the electric field while for strong fields, the Stark shift of the energy groundstate increases almost linearly with the electric field. There is a transition for quasi-one dimensional to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Vazquez et al 46 has studied the variation of the shift of electron energy as a function of the dot radius for various electric fields. In their investigation it is found that for electric fields of about ten atomic units there is negligible shift of the electron energy for dot sizes up to about one and half 47 that the mutual cancellation of the sum of the piezoelectric and the spontaneous polarization in wurtzite ZnO dot-matrix structure leads to the negligible internal field.…”
Section: Theorymentioning
confidence: 99%
“…Vazquez et al 46 has studied the variation of the shift of electron energy as a function of the dot radius for various electric fields. In their investigation it is found that for electric fields of about ten atomic units there is negligible shift of the electron energy for dot sizes up to about one and half 47 that the mutual cancellation of the sum of the piezoelectric and the spontaneous polarization in wurtzite ZnO dot-matrix structure leads to the negligible internal field.…”
Section: Theorymentioning
confidence: 99%
“…When the external fields are present, the spherical symmetry is violated and, therefore, calculation of the energy spectrum becomes complicated due to the fitting conditions at the interfaces. The influence of electric field on properties of nanosystems is described by the linear term with respect to the electric field in the Schrödinger equation for electron, so the problem can be solved using the variational method or perturbation theory for a simple spherical quantum dot [17,18] and spherical layer [19,20]. In the article [17], the Stark shift is calculated using the variational method within the framework of the infinite confining potential well model for electron in the spherical quantum dot.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of electric field on properties of nanosystems is described by the linear term with respect to the electric field in the Schrödinger equation for electron, so the problem can be solved using the variational method or perturbation theory for a simple spherical quantum dot [17,18] and spherical layer [19,20]. In the article [17], the Stark shift is calculated using the variational method within the framework of the infinite confining potential well model for electron in the spherical quantum dot. The authors of [18] investigated intersubband absorption spectra in the simple spherical quantum dot with definite walls with or without hydrogen on-center impurity.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it results that these electrostatic forces, and even Casimir force, have influence on the mechanical properties of cantilevers very dependent on the geometry of the cantilever tip [22]. Following this motivation and the experience obtained in the study of Stark effect with variational techniques in several geometries [7,8,23], we decided to study this effect in the tip of a typical cantilever of an atomic force microscope (AFM) using as a first approximation the geometry given by a wedge since, as a matter of fact, there exist commercial triangular-shaped silicon microcantilevers (Thermomicroscopes) [24].…”
Section: /23mentioning
confidence: 99%